Evaluation of the Psychiatric Disorders among Amphetamine Addicts in Rehabilitation Centers: A Cross-Sectional Analysis - Saud D. AlOtaibi; Hossam A. Elsisi; Mohammed J. AlShammary; Saud A. AlQader; Hejab A. AlHarbi; Bayan R. AlOlaiyan; Ahmad O. Alanazi; Firas S. AlMendeel; Yazeed N. AlHarbi; Ibrahim AlKhalaf; Ahmad H. Alhowail; Abdelhamid Mohamed Elwy; et al. (Journal of Toxicology)
Background. People who are addicted to amphetamines have a much greater chance of developing psychosis compared to those who are not. It is essential to study the behavioral and psychological effects of amphetamines. Therefore, this research aimed to examine conditions such as depression, anxiety, mood, cognitive abilities at the workplace, and social responsibilities by using sociodemographic factors as useful tools in determining effective strategies for preventing, managing, and treating amphetamine addiction. Methods. A cross-sectional study among addicts hospitalized at two rehabilitation centers across Saudi Arabia between May and October 2023. A validated questionnaire consisting of psychiatric disorders assessment tools was distributed to healthcare professionals to start an interview with addicts to assess the abnormalities. The results were compared with healthy people (control). The assessment tools used are Hamilton Anxiety and Depression Rating Scale, Young Mania Rating Scale, and Work and Social Adjustment Scale. The data were analyzed using SPSS version 22.0. Pearson correlation coefficients (r) were employed. Results. A total of 60 subjects participated in this study. The participants were divided into two groups (n = 60): group I was control (n = 25) healthy volunteers and group II was amphetamine abusers (n = 35), who were hospitalized for detoxification. The ages ranged from 18 to 60 years old with mean ages of 38.68 (±8.14) and 37.77 (±10.95) years in the control and amphetamine groups, respectively. Among the addicts, the mean severity dependence scale value was 10.46 (±1.82), which denotes high dependency on the illicit drug. The prevalence of high levels of anxiety, depression, and bipolar disorder was significantly higher among addicts when they were compared to healthy people (control). The assessment of the Work and Social Adjustment Scale (WSAS) reflected a higher impairment that minimized their ability to perform the work requirements, home management, social leisure, and relationships. Conclusions. The addiction to amphetamines was associated with high impairment of work performance and social obligations and a negative impact on the addict’s mental health. The risk of suffering anxiety, depression, and bipolar is higher than in nonaddict people. These effects are attributed to brain damage, neurotoxicity, and neuronal inflammation, particularly when these substances are abused over extended periods and at higher doses.